Penerapan Model PjBL untuk Meningkatkan Keaktifan Siswa pada Pembelajaran IPA Materi Ekosistem Kelas V SD - Rahma, Fitri Nur; Kurniawati, Wahyu; Purnomo, Heru (Paedagogie, 2024)
This research aims to apply the Project Based Learning (PjBL) model to increase student activity in learning science and ecosystem material in class V elementary school. The PjBL method used involves students in a project to make ecosystem dioramas, which is carried out in groups. Each group was assigned to make dioramas of various types of ecosystems such as marine ecosystems, savanna, tundra and tropical rainforest. The learning process includes an introduction to ecosystem concepts, research and analysis, as well as presentation and discussion of student work. From the research results, the data shows a significant increase in student activity from 25% in the pre-cycle to 75% in the first cycle. PBL helps overcome boredom in traditional teacher-centered learning methods, encouraging students' activeness, creativity, deep understanding of ecosystems, and communication and collaboration skills. This approach has proven to be effective in increasing the activeness and quality of science learning in the classroom. The application of the PJBL model in science learning with ecosystem material has proven to be effective in increasing students' activeness, creativity, communication and collaboration. This approach not only triggers students to be more active in learning, but also provides a deeper understanding of the ecosystem, as well as developing skills that are important for their future. Therefore, PJBL can be a very effective learning strategy, especially in science subjects.